Pemberdayaan Masyarakat Adat Melalui Literasi Digital: Melindungi Warisan Budaya Takbenda dan Mendorong Inklusi Pendidikan - Yuni Afita Sari; Muhammad Arief Virgy (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2024)
This study examines the role of digital literacy in safeguarding intangible cultural heritage, focusing on the cultural exploitation of the Baduy Luar indigenous community on TikTok. The commodification of culture in digital media often leads to misrepresentation, highlighting the importance of digital literacy as an empowerment tool. Using a literature review and case study approach, this research emphasizes the need for inclusive digital literacy programs to enable indigenous communities to control cultural representation, understand their rights to Indigenous Cultural and Intellectual Property (ICIP), and counter the dominance of Authorized Heritage Discourse (AHD) in digital narratives. Findings reveal that community-based digital literacy can support cultural preservation, enhance educational access, and protect indigenous communities from digital exploitation. Through stakeholder collaboration and the enactment of ICIP regulations, digital literacy can serve as a strategic tool to safeguard indigenous cultural heritage, to promote educational inclusion, and to ensure the sustainability of cultural heritage in the digital age.